Evolution of the active site of human glutathione transferase A2-2 for enhanced activity with dietary isothiocyanates - Zhang, Wei; Dourado, Daniel F.A.R.; Mannervik, Bengt (Biochimica et biophysica acta, 2015)
Organic isothiocyanates (ITCs) are produced by plants, in which they are released from glucosinolates by myrosinase. ITCs are generally toxic and serve as a chemical defense against herbivorous insects and against infections by microorganisms. In mammalian tissues subtoxic concentrations of ITCs can provide protective effects against cancer and other diseases partially by induction of glutathione transferases (GSTs) and other detoxication enzymes. Thus, human consumption of edible plants rich in ITCs is presumed to provide health benefits. ITCs react with intracellular glutathione to form dithiocarbamates, catalyzed by GSTs. Formation of glutathione conjugates is central to the biotransformation of ITCs and leads to a route for their excretion. Clearly, the emergence of ITC conjugating activity in GSTs is essential from the biological and evolutionary perspective. In the present investigation an active-site-focused mutant library of GST A2-2 has been screened for enzyme variants with enhanced ITC activity. Significantly superior activities were found in 34 of the approximately 2000 mutants analyzed, and the majority of the superior GSTs featured His and Gly residues in one of the three active-site positions subjected to mutagenesis. We explored the propensity of GSTs to obtain altered substrate selectivity and moreover, identified a specific pattern of mutagenesis in GST for enhanced PEITC detoxification, which may play an important role in the evolution of adaptive responses in organisms subjected to ITCs. The facile acquisition of enhanced ITC activity demonstrates that this important detoxication function can be promoted by numerous evolutionary trajectories in sequence space.